Effect of low protein diet with balanced amino acids with protease on performance and litter quality of commercial broiler - ROKADE, J J; THYAGARAJAN, D; OMPRAKASH, A V; KARUNAKARAN, R (The Indian Journal of Animal Sciences, 2014)
An experiment was carried out to evaluate nutritional interventions to minimize nitrogen excretion in broilers. Three dietary treatments with 42 birds each were subjected to standard protein diet (T1), low protein with balanced amino acids (T2) and low protein with balanced amino acids plus enzyme (T3). Production performance (body weight, feed efficiency and liveability) and litter quality was assessed on second, fourth and sixth week of age. No significant difference was noticed in body weight, liveability and feed efficiency between treatment and control groups. Statistical analysis also revealed that treatments with high protein (T1) had high pH, moisture and litter nitrogen value. The present study revealed that low protein diet with balanced amino acid profile plus protease supplementation can minimize nitrogen excretion in litter without affecting production performance of the bird and also a cost effective approach.